A geometric approach to cosmological boundary conditions - Savi, L. L [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The observed T-asymmetry of macroscopic physics is traced back to the extremely low entropy conﬁguration of the early universe. Although matter was very hot and with a uniform temperature at that stage, the gravitational degrees of freedom were largely suppressed, which fact contributes to the lowness of the entropy and is encoded in the high level of spatial symmetry (nearly Friedman-Lemître-Robertson-Walker character) of the last scattering surface. I analyze diﬀerent attempts to explain the origin of such special conﬁguration. The inﬂation paradigm is probed with respect to this problem, and it is concluded that the initial low entropy cannot be accounted for within it. Similar conclusions are reached with respect to statistical (i.e. anthropic) reasonings. On the other hand, the paradigm known as conformal cyclic cosmology (CCC) presents itself as a new alternative which surpasses many of the diﬃculties faced by its rivals, although raising its own open questions. I introduce the model together with the mathematical structure of Cartan geometries as a possible means of achieving a better understanding of cosmological boundary conditions. One element which is crucial in this analysis is the modeling of the Cartan geometric structure over a de Sitter space SOe(4,1)/SOe(3,1) with varying length parameter. The introduction of a length parameter in the kinematics is favored by the observation of a positive cosmological constant and also desirable for quantum gravity reasons, due to the natural scale set by Planck's constant

A assimetria temporal observada na física macroscópica se deve à conﬁguração de entropia extremamente baixa do universo primordial. Apesar de a matéria estar muito quente e com uma temperatura uniforme naquele estágio, os graus de liberdade gravitacionais estavam em grande medida suprimidos, fato este que contribui para o baixo valor da entropia e está codiﬁcado no alto grau de simetria espacial (caráter aproximadamente Friedman-Lemaître-Robertson-Walker) da superfície de último espalhamento. Analisamos diferentes tentativas de explicar a origem de tal conﬁguração especial. O paradigma inﬂacionário é testado com respeito a esse problema, e é concluído que a baixa entropia inicial não pode ser explicada dentro dele. Conclusões similares são obtidas com respeito a formulações estatísticas (i.e. antrópicas). Por outro lado, o paradigma conhecido como cosmologia cíclica conforme (CCC) se apresenta como uma nova alternativa que ultrapassa muitas das diﬁculdades enfrentadas pelos seus rivais, apesar de levantar suas próprias questões em aberto. Introduzimos o modelo juntamente com a estrutura matemática das geometrias de Cartan como um meio possível de atingir um melhor entendimento das condições de contorno cosmológicas. Um elemento que é crucial nessa análise é a modelagem de uma estrutura geométrica de Cartan sobre o espaço de de Sitter SOe(4,1)/SOe(3,1) com um parâmetro de comprimento variável. A introdução de um parâmetro de comprimento na cinemática é favorecida pela observação de uma constante cosmológica positiva e também desejável por motivos oriundos da gravitação quântica, devido à escala natural determinada pelo comprimento de Planck
Keywords: Cosmologia; Gravitação; Cinematica; Cosmology